What do we know about rosacea? - pathophysiology and treatment - Dalmata, Weronika; Gąbka, Ilona; Dąbrowski, Jan; Szarpak, Julita; Lipiec, Marta; Mielniczek, Katarzyna; Piwoński, Michał (Journal of Education, Health and Sport, 2022)
Introduction: rosacea affects approximately 10% of the world's population. It is a recurrent, inflammatory dermatosis that is difficult to deal with despite treatment. Material and methods: literature review from PubMed databases from 2017-2022. Conclusions: It is very difficult to find the cause of acne lesions. What is certain is that various factors overlap: genetic, environmental, immunological disorders, intestinal abnormalities, dietary factors. New treatments are constantly being sought. The overall health of the organism is very important in maintaining the proper function of every organ, but also of the skin - as a barrier against rosacea.